Prevalence of maxillary sinusitis attributed to odontogenic causes in a chilean subpopulation: a cross sectional study - Peña-Bengoa, Fernando; Diaz, Juan; Niklander , Sven Eric; Guerrero, Constanza; Cáceres, Carolina; Rodríguez-Luengo , Macarena; Meléndez, Patricio (Brazilian Dental Science, 2025)
Background: Odontogenic maxillary sinusitis is a condition caused by dental infections attributed to the close anatomical proximity that maxillary posterior teeth have with the maxillary sinus. Distinguishing odontogenic sinusitis from other types of sinusitis is crucial for its accurate treatment, avoiding improper treatments and multiple consultations. Objective: To analyze the prevalence of maxillary sinusitis attributed to odontogenic causes in a Chilean Subpopulation using cone-beam computed tomography (CBCT) scans. Material and Methods: One hundred and thirty-nine CBCT scans from patients with a previous radiological diagnosis of maxillary sinusitis were evaluated. Using a multiplanar and panoramic reconstruction, the thickening of one or both maxillary sinus mucosa was evaluated. The thickness of the sinus mucosa, together with the presence of associated dental pathologies and/or conditions were also evaluated using sagittal and coronal sections. Results: Of the 139 cases, 54.6% presented a unilateral thickening of the sinus membrane. Of those, 72.4% were associated with odontogenic factors, indicative of odontogenic sinusitis. The most frequent cause was apical periodontitis (23.4%), followed by endodontically treated teeth (21.1%). Bilateral mucosal thickening was observed in 45.4% of all cases. Within this subset, 46% displayed symmetrical mucosal thickening, while 54% showed disparities exceeding 2 mm. Among these, 44.1% had a superimposed dental pathology attributable to uneven increased mucosal thickness. Conclusion: Odontogenic etiology is a common cause of maxillary sinusitis, mainly associated with apical lesions and endodontically treated teeth. The overlay of dental pathology onto bilateral mucosal thickening patients can result in an exacerbation of the inflammatory state within the affected sinus membrane. KEYWORDS Chronic sinusitis; Cone beam computed tomography; Maxillary sinus; Odontogenic sinusitis; Schneider’s membrane.